Study of axi-symmetric vibrations in a micropolar transversely isotropic layer - Gupta, Raj Rani; Gupta, Rajani Rani (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation deals with the propagation of circular crested Lamb waves in a homogeneous micropolar transversely isotropic medium. Secular equations for symmetric and skew-symmetric modes of wave propagation in completely separate terms are derived. The amplitudes of displacements and microrotation are computed numerically for magnesium as a material and the dispersion curves, amplitudes of displacements and microrotation for symmetric and skew-symmetric wave modes are presented graphically to evince the effect of anisotropy. Some special cases of interest are also deduced.
Keywords: micropolar; transversely isotropic; amplitude ratios